Analysis between Platelet Count and Blood Groups in Apheresis Platelet Donors with Demographic Features - Canan Eren; Serpil Çeçen (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2019)
Platelet transfusion is used to prevent bleeding in patients with thrombocytopenia or platelet dysfunction. Purpose of investigating demographic characteristics of eligible volunteers as platelet donors and of demonstrating the association of platelet counts with blood groups as well as other factors. We used data of individuals who referred to a blood center in our hospital. Age, body weight, body mass index (BMI), and gender were determined, and than hemogram values such as leukocyte, hemoglobin, hematocrit, and platelet and ABO blood types of those individuals were identified. A statistically significant difference determined for height, body weight, and BMI in both genders. Although BMI was lower in the group of platelet count ≤ 250, it was higher in a group of platelet count > 250. Furthermore, platelet count was more moderate in blood group O Rh-positive but, no significant difference was group O Rh-negative. Platelet count was higher in other Rh-positive blood groups than Rh negatives. BMI is vital in apheresis donors, and individuals with higher BMI values may prefer in case of double dose or more apheresis need. The determination of platelet counts in Rh positives is more elevated than Rh negatives.